SOLARAQ: a start-up of solar power solutions in Iraq - Alzubaidi, Muhammad Lutfi Ibrahim (2023)
This business plan will be analyzing setting up a startup for a solar energy solutions provider called SOLARAQ. It is a solar energy solutions company that is situated in Baghdad, Iraq. The company also has two other branches in Mosul and Basra, covering all regions within the country. SOLARAQ is specialized in selling and installing solar PV systems and other solar products like solar heaters and air conditioners. The company offers a free consultation and house inspection for potential buyers to deliver the maximum benefit and smoothest experience to the customers. The company will start with one branch in year 1 and will be expanding in the second year to have an overall three branches, in addition to having external sub-sellers spread across other cities.